Analysis Waste Level of Column Reinforcement Work Planning with Software Cutting Optimization - Jagad, Sulthanul Auliya; Putra, I Nyoman Dita Pahang (CogITo Smart Journal, 2024)
In the era of globalization, construction development in Indonesia has experienced significant acceleration, accompanied by innovation in its implementation methods. One of the main problems in construction projects is material waste, especially in column work. This study aims to analyze the level of waste in column reinforcement work by applying the cutting optimization method using Cutting Optimization Pro software and analyzing the diameter of the reinforcement that produces the greatest waste. The research method used is quantitative by analyzing secondary data through shop drawings and detailed standards from construction projects. The study was conducted on column work from Ground to Floor 5 by calculating material requirements using the Bar Bending Schedule and optimizing cutting patterns through Cutting Optimization Pro Software. The results show that the lowest percentage of waste D16 is 0%, the highest at Ø8 is 2.653%, and the overall average waste is 0.916%. This study provides new insights into the importance of innovation in material planning and management in the construction industry. By utilizing optimization software, contractors can improve efficiency and reduce the impact of material waste. This study is expected to be a reference for contractors in adopting new technologies in the management of material waste.